Sustainable Development of the Regional Economy: Indicators, Analysis, Systematization - VOROBYOV, Yuriy Nikolayevich; BURKALTSEVA, Diana Dmitrievna; KOVALYOVA, Irina Nikolaevna; BORSCH, Lyudmila Mihaylovna; GERASIMOVA, Svetlana Vasilyevna (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018, 2018)
The goal of the study is to assess the sustainability of the development of regional economic clusters in the territorial socioeconomic system given the three interrelated components: the cluster development strategy, a set of indicators, and an institutional component. General scientific methods of research, comparative, technical and economic analysis, expert assessments and forecasting, regional economy, cluster theory and resource management were applied to solve the research problems. The key findings of the study are as follows: The method presented in the paper is a tool for assessing the resource potential of regional clusters in order to ensure their sustainable development within the territorial socioeconomic system; Practical application of the developed model allowed to quantify the sustainability of the regional clusters development in the Karachaevo-Cherkess Republic and to define the efficiency of using production, financial and infrastructural resources in achieving added value growth by the cluster participants; Dynamics of the integral indicator of sustainable development of regional clusters of the Karachaevo-Cherkess Republic indicates the activation of cluster initiatives in this region and the increase in the efficiency of the cluster participants; Findings of the study unveiled the need for transition to innovative network strategy for the development of regional clusters in the Karachaevo – Cherkess Republic, intensification of investment activities in the fields of agriculture, construction, mining, recreation, and tourism.